Sociocultural Adaptation in Immigrant University Students and Its Association with Health-Promoting and Risk Behaviors: A Public Health Perspective - Merve Özgölet; Kamer Gür (Fenerbahçe Üniversitesi Sağlık Bilimleri Dergisi, 2026)
Migration can be defined as the movement of people from one place to another for various reasons, including economic, social, political, educational, or security-related factors. The causes of migration have taken many different forms throughout history. Over the past 15 years, migrants and migration have become increasingly significant issues for Turkey. Although Turkey has long been a home to diverse cultures, it has faced greater challenges in recent years due to the new cultural dynamics that migration brings with it. Migration leads to various changes both in the host country and in the migrants themselves. Being able to adapt to the culture of the host country can ease economic, social, and psychological burdens, ultimately improving the quality of life for migrants. At the same time, greater adaptation to the host country may also facilitate access to risk-taking behaviors. The aim of this review is to examine the relationship between sociocultural adaptation and health-promoting versus risk behaviors among immigrant university students from a public health perspective. To this end, current national and international literature was reviewed in detail using Google Scholar, Medline, and PubMed databases, and several evidence-based recommendations are offered to support the sociocultural adaptation of migrants.